Concepts We Transform by : Metaphorical Concepts in Post-COVID-19 Transition to Normalcy - Pankakoski, Timo (Helsinki University Press, 2025)
This article tackles key terminology of the post-COVID-19 transition to normalcy from a conceptual and metaphor analysis viewpoint. Scholarship has covered the pandemic’s linguistic ramifications, but the conceptual basis of its aftermath remains neglected. Which terms and underlying metaphors are used to conceptualize the transition from the societal crisis to normalcy and to assess its success? Where do these come from, and what are their key merits and shortcomings? How consistent are they, and what kind of future do they predict for us? I focus on demobilization, rebuilding, resilience, and recovery—key terms from the transnational regulative discourse manifesting on international, European, and national levels alike. By assessing these concepts’ uses and connotations, my article highlights the post-pandemic transition’s political nature and promotes a more aware normalization. I analyze resilience as a central concept in the European post-pandemic transition: it is open to alternative interpretations and typically carries forward-looking transformative power. This is aptly doubled by a transformative, rather than restorative, notion of recovery, which carries significant future expectations. Rather than merely regaining operational capacities, societies are expected to improve while recovering—an aspect reflected in the terminology of ‘building back better’ and in framing resilience as an exponentially increasing ability for better future recovery. Normatively, such transformative aims, however, clash with the underlying metaphor of society as a patient recovering from a disease. The article proposes a more moderate notion of nonmedical recovery of society as gaining a novel, adjusted self-understanding as a fully operative entity with a problematic past.